Five go down to the sea - Blyton, Enid. (b, 2004)
Why would anyone deliberately lure sailors on to the dangerous Cornish rocks along the coast at night? Who is flashing lights from the old tower in the wild and stormy weather? Can the FAmous Five uncover the truth-- before somebody gets hurt?
Keywords: Famous Five (Fictitious characters) -- Juvenile fiction; Mystery and detective stories